Case report: Desmoid fibromatosis diagnosed in a 27-year-old male after being mistaken for a gastrointestinal stromal tumour - Albino, Larissa; Guo, Yimeng; Bacani, Julinor; Mather, Cheryl; Nilsson, Jan-Erick; Dieleman, Levinus A. (Frontiers in Medicine, 2022)
Despite being distinct lesions, gastrointestinal stromal tumours (GISTs) and desmoid fibromatosis may appear similar on imaging when they involve the stomach wall or bowel. As a result, they may be confused with one another when initially diagnosed. This report aims to present a case where a desmoid tumour was mistaken for a gastric GIST in a 27-year-old gentleman despite extensive investigation prior to exploratory laparotomy, and why differentiation through pathology, with a focus on the immunohistochemistry profile, is key for proper prognostication and appropriate management, including timely investigation for associated diseases such as Familial Adenomatous Polyposis in patients with desmoid tumours.